A new on-line ultrasonic thickness monitoring system for high temperature pipes. (October 2022) - Song, Jiahe; Guo, Donghui; Jia, Jiuhong; Tu, Shandong
Abstract: On-line thickness monitoring of pipe wall is very important in petrochemical and power generation industries. There are two main reasons that the conventional ultrasonic transducers cannot withstand long-term on-line monitoring in high temperature. One is that the piezoelectric elements within transducers depolarize causes them to fail, the other is that the working medium inside the pipeline interferes with the ultrasonic wave results in the decline of measurement accuracy. In order to overcome these problems, an ultrasonic thickness gauge using a waveguide that can sustain a large temperature drop and effectively transmit the quasi-fundamental shear horizontal (SH0*) wave without causing dispersion is designed. The waveguide can isolate the vulnerable piezoelectric sensor from the high-temperature measurement zone, and the SH0* wave can avoid interfere of the working medium. Moreover, a monitoring system applying this ultrasonic thickness gauge is discussed and the application method of this system is introduced. The high temperature long-term reliability experiments carried out both in laboratory and on-site, and wall thinning measurement by corrosion experiments show that the designed thickness gauge has good accuracy and long-term stability, which can meet the needs of long-term on-line monitoring of high temperature pipes. Highlights: On-line ultrasonic thickness monitoring system. Ultrasonic thickness gauge. Quasi-fundamental shear horizontal wave. Structural health monitoring of high temperature pipes.